Enhancing International Education with Generative AI: From Recruitment to Academic and Cultural Support - Siddiqi, Muddassir (American Journal of STEM Education, 2024)
This study explores the potential of Generative Artificial Intelligence (GAI) to enhance U.S. higher education’s competitiveness in attracting international students (over 1 million in 2022-23). By streamlining admissions, personalizing academic support, and fostering cultural integration, GAI can improve student experiences. Automating admissions, offering real-time application guidance, and providing language translation are highlighted as potential applications. Additionally, data-driven recruitment strategies powered by GAI are explored.